Metal-coated organic silicon elastomer microsphere as well as preparation method and application thereof

By performing functional group modification and reduction reactions on the surface of silicone elastomer microspheres, the problem of insolid composite of silicone microspheres and metals is solved, and the preparation of lightweight, high conductivity and temperature-resistant silicone-metal composite materials are realized.

CN119529328APending Publication Date: 2025-02-28JIANGSU YONGXIN MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411513410.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, silicone elastomer microspheres and metal components are not firmly combined and cannot meet the use requirements.

Method used

By modifying functional groups on the surface of the silicone elastomer microspheres, including the introduction of functional groups such as primary amine groups, secondary amine groups, and tertiary amine groups, and contacting with an aqueous solution containing a metal salt and a reducing agent, the reduction reaction is carried out to complete the deposition and coating of the metal.

Benefits of technology

The stable composite of silicone elastomer microspheres and metals has been achieved, and a lightweight, high and low temperature resistance and good conductivity silicone-metal composite material is prepared, which is suitable for conductive coatings, conductive glues and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529328A_ABST
    Figure CN119529328A_ABST
Patent Text Reader

Abstract

The invention provides a metal-coated organic silicon elastomer microsphere as well as a preparation method and application thereof, and the preparation method comprises the following steps: performing functional group modification on the surface of the organic silicon elastomer microsphere containing carbon-carbon double bonds and hydroxyl on the surface; the functional groups comprise one or more of primary amino, secondary amino, tertiary amino, carboxyl, sulfydryl, sulfenyl, hydroxyl and carbonyl; and then contacting with an aqueous solution containing metal salt and a reducing agent and carrying out reduction reaction to finish deposition and / or coating of metal on the surfaces of the organic silicon elastomer microspheres. The metal-coated organic silicon elastomer microspheres prepared by the invention are organic silicon elastomer-silver composite microspheres, have the advantages of light weight, high and low temperature resistance, aging resistance, high conductivity, hard shell and soft core, high sphericity and good fluidity, and are greatly reduced in cost; the application in the aspects of conductive coatings, conductive adhesives, low-temperature photovoltaic silver paste, electromagnetic shielding, heat conduction and toughening can be well met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of functional microspheres, and in particular to a metal-coated organic silicon elastomer microsphere and a preparation method and application thereof. Background Art

[0002] Silicone elastomer is a kind of polymer material composed of silicone molecules. Its basic structural unit is composed of silicon-oxygen chain links, and the side chains are connected to various other organic groups through silicon atoms. This structure makes it combine the characteristics of organic matter with the functions of inorganic matter. Silicone elastomer has many advantages such as high temperature resistance, low temperature resistance, aging resistance, not easy to swell (except benzene solvents), low specific gravity, good low temperature elasticity, low glass transition temperature, physiological inertness, etc. If silicone elastomer microspheres are used as templates and silver, nickel, zinc, gold and other metals are firmly connected to their surfaces, lightweight silicone-metal composite materials with excellent comprehensive performance can be prepared, which can be used in many fields such as electrical conduction, thermal conduction, toughening, electromagnetic shielding, etc.

[0003] However, since the surface energy of the silicone elastomer material itself is very low and it is difficult to compound with metal, it is difficult to find silicone-metal composite microspheres on the market. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a metal-coated silicone elastomer microsphere and a preparation method and use thereof, so as to solve the problem that the silicone elastomer microsphere and the metal component are not firmly composited in the prior art and cannot meet the use requirements.

[0005] To achieve the above-mentioned purpose and other related purposes, the present invention is implemented by including the following technical solutions.

[0006] The first aspect of the present invention provides a method for preparing metal-coated silicone elastomer microspheres, comprising the following steps:

[0007] Performing functional group modification on the surface of the organosilicon elastomer microspheres containing carbon-carbon double bonds and hydroxyl groups on the surface, wherein the functional groups include one or more of primary amine groups, secondary amine groups, tertiary amine groups, carboxyl groups, thiol groups, sulfhydryl groups, hydroxyl groups, and carbonyl groups;

[0008] Then, the microspheres are contacted with an aqueous solution containing a metal salt and a reducing agent to undergo a reduction reaction, thereby completing the deposition and / or coating of the metal on the surface of the organic silicon elastomer microspheres.

[0009] Preferably, after the reduction reaction is completed, solid-liquid separation is performed.

[0010] Preferably, the functional group modification is accomplished by grafting and / or copolymerization.

[0011] More preferably, the functional group is modified as follows:

[0012] a) grafting or copolymerizing the grafted material with the carbon-carbon double bond;

[0013] And / or, b) using the hydroxyl groups on the surface of the silicone elastomer microspheres as the binding points, treating the silicone elastomer microspheres having carbon-carbon double bonds and hydroxyl groups on the surface with one or both of nitrogen-containing silanes and sulfur-containing silanes to introduce amine groups and / or sulfur elements.

[0014] In the above modification methods in the present application, all the functional groups are chemically bonded to the main chain of the silicone elastomer molecule, and the bond is firm, and the metals used, such as silver, nickel, zinc and their oxides, can be well combined with the above functional groups, thereby completing the complete and dense coating of the functionalized silicone elastomer microspheres by metallic silver.

[0015] Preferably, the grafted substance is selected from monomers containing one or more of a primary amine group, a secondary amine group, a tertiary amine group, a thiol group, an olefin group, a hydroxyl group, an amide group, and a carbonyl group.

[0016] Preferably, in a), an initiator is used to initiate the polymerization, and the initiator is selected from one or more of high-energy radiation source irradiation, water-soluble persulfate initiator, oxidation-reduction initiation system, water-soluble azo initiator, and thermal initiation polymerization.

[0017] Preferably, the nitrogen-containing silane is selected from any one or more of the following: 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-n-butyl-3-aminopropyltrimethoxysilane, N-n-butyl-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, One or more of silane, 3-anilinopropyl trimethoxysilane, 3-anilinopropyl triethoxysilane, 3-(N-cyclohexylamino)propyl trimethoxysilane, 3-(N-cyclohexylamino)propyl triethoxysilane, 3-(N-cyclohexylamino)propyl methyldimethoxysilane, 3-(N-cyclohexylamino)propyl methyldiethoxysilane, 3-ureapropyl trimethoxysilane, 3-ureapropyl triethoxysilane, N,N-dimethyl-3-aminopropyl trimethoxysilane, N,N-diethyl-3-aminopropyl trimethoxysilane, 3-(diethylenetriamine)propyl trimethoxysilane, and N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane. Taking into account low cost, availability, easy hydrolysis and stability after hydrolysis, in a more preferred embodiment, the nitrogen-containing silane is selected from 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and 3-ureapropyltrimethoxysilane.

[0018] Preferably, the sulfur-containing silane is selected from any one or more of the following: bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-thiocyanatopropyltriethoxysilane, 3-thiocyanatopropyltriethoxysilane, 3-octanoylthiopropyltrimethoxysilane, 3-octanoylthiopropyltriethoxysilane, and the structural formulas are respectively Silane containing both nitrogen and sulfur elements has the structural formula Silanes containing both nitrogen and sulfur, where R 1 is a straight or branched saturated hydrocarbon group containing 3 to 12 carbon atoms, R 2 is methyl or ethyl, R is methyl or ethyl; n is an integer from 2 to 10.

[0019] Preferably, the metal element in the metal salt is one or more of silver, nickel or zinc. More preferably, the metal element is silver.

[0020] Preferably, the reducing agent is one or more selected from hydrazine hydrate, sodium borohydride, dimethylamino borane, formaldehyde, acetaldehyde, glucose, ascorbic acid, tartaric acid, glycerol, ferrous sulfate, sodium hypophosphite, sodium hypophosphite, hydrogen peroxide and sodium sulfite.

[0021] Preferably, the aqueous solution containing the metal salt and the reducing agent further contains one or both of a stabilizer and a complexing agent. More preferably, the stabilizer is selected from one or more of polyvinyl pyrrolidone, arabic plastic, polyvinyl alcohol, sodium citrate, and sodium thiosulfate. More preferably, the complexing agent is selected from one or more of ammonia water, ethylenediamine, hexamethylenediamine, triethylamine, n-butylamine, alcohol amines, sodium citrate, potassium sodium citrate, disodium EDTA, citric acid, tartaric acid, gluconic acid, malic acid, and lactic acid.

[0022] Preferably, the preparation method of the silicone elastomer microspheres containing carbon-carbon double bonds and hydroxyl groups on the surface is:

[0023] Vinyl polysiloxane, hydrogen-containing polysiloxane, curing retarder and platinum group metal catalyst are mixed, and allyl methacrylate or allyl acrylate is added during the mixing, and the mixture is emulsified and subjected to addition reaction in water to obtain the product.

[0024] In the present application, polysiloxane containing vinyl groups is referred to as vinyl silicone oil. The vinyl groups can be located at both ends, one end, or on the side chain of the polysiloxane molecular chain, and all vinyl groups are directly connected to silicon (Si).

[0025] In the present application, polysiloxane containing silicon hydrogen groups is referred to as hydrogen-containing polysiloxane or hydrogen-containing silicone oil. The hydrogen bonds can be located at both ends, one end, or on the side chain of the polysiloxane molecular chain, and all hydrogen groups are directly connected to silicon (Si).

[0026] More preferably, the viscosity of the composition formed by the vinyl polysiloxane and the hydrogen-containing polysiloxane at 25°C is not more than 100,000 mm 2 / s. Because when the viscosity exceeds 100,000mm 2 / s, it is impossible to prepare particles with small particle size and narrow distribution. The viscosity value is measured by a rotational viscometer. More preferably, the viscosity of the composition of the vinyl polysiloxane and the hydrogen-containing polysiloxane at 25°C is 50 to 10000 mm 2 Most preferably, the viscosity of the composition of vinyl polysiloxane and hydrogen polysiloxane at 25° C. is 50 to 10000 mm 2 / s, such as 50, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400 00, 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, or 10000.

[0027] In the above addition curing process, the allyl group completes the addition reaction with the hydrogen-containing polysiloxane, and the methacrylate group or acrylate group will remain on the surface of the microspheres as a grafting point in the aqueous system due to its low addition activity and high polarity. Reaction formula:

[0028] CH2=C(CH3)COOCH2CH=CH2+H-Si≡–>CH2=C(CH3)COOCH2CH2CH2-Si≡

[0029] CH2=CHCOOCH2CH=CH2+H-Si≡–>CH2=CHCOOCH2CH2CH2-Si≡.

[0030] Preferably, the total amount of allyl methacrylate and / or allyl acrylate added is 0.5-20wt%, preferably 1-10wt%, and more preferably 1-5wt%, based on the total mass of the vinyl polysiloxane and the hydrogen-containing polysiloxane. If too much allyl methacrylate and / or allyl acrylate is added, the odor is strong during the production process and the product has a strong residual taste; if too little is added, there are too few grafting points, which is not conducive to the subsequent grafting and copolymerization.

[0031] Preferably, the ratio of the molar number of hydrogen bonds in the hydrogen-containing polysiloxane to the molar number of vinyl groups in the vinyl polysiloxane is greater than 1:1. Ensure that the hydrogen bonds are in excess, so that after the completion of the hydrosilylation reaction, in a water environment, the excess hydrogen bonds are catalyzed by platinum to become silanol groups, and the reaction formula is:

[0032] ≡Si-H+CH=CH-Si≡–>Si-CH2-CH2-Si≡

[0033] ≡Si-H+H2O–>≡Si-OH+H2.

[0034] More preferably, the ratio of the molar number of hydrogen bonds in the hydrogen-containing polysiloxane to the molar number of vinyl groups in the vinyl polysiloxane is in the range of 1.01 to 50: 1; preferably 1.2 to 2: 1; more preferably 1.4 to 1.6: 1. If there are too many hydrogen bonds, it will lead to too much hydrogen release, which is dangerous; while too few hydrogen bonds will result in too few hydroxyl groups being generated, which is not conducive to the remaining reactions.

[0035] Preferably, based on the total weight of the vinyl polysiloxane and the hydrogen-containing polysiloxane, the amount of the curing retarder added is 0.01 to 5 wt %.

[0036] Preferably, the curing retarder is selected from one or more of an alcohol derivative with a carbon-carbon triple bond, an ene-yne ​​compound, an alkenyl-containing polysiloxane, an amide compound, and a maleate compound. More preferably, the alcohol derivative with a carbon-carbon triple bond is selected from one or more of 3-methyl-1-butyne-3-ol, 3-methyl-1-pentyne-3-ol, 3,5-dimethyl-1-hexyne-3-ol, 3-phenyl-1-butyne-3-ol, and 1-ethyn-1-cyclohexyl alcohol. More preferably, the ene-yne ​​compound is selected from one or two of 3-methyl-3-pentene-1-yne, 3,5-dimethyl-3-hexene-1-yne. More preferably, the alkenyl-containing low molecular weight polysiloxane is selected from one or two of tetramethyltetravinylcyclotetrasiloxane and tetramethyltetrahexenylcyclotetrasiloxane. More preferably, the amide compound is selected from one or more of N,N-diallylformamide, N,N-diallylbenzamide, N,N,N',N'-tetraallylphthalamide, N,N,N',N'-tetraallylterephthalamide, and N,N,N',N'-tetraallylisophthalamide. More preferably, the maleate compound is selected from one or more of monoethyl maleate, monoallyl maleate, mono-2-ethylhexyl maleate, and diallyl maleate. More preferably, the polyvinyl polysiloxane curing retarder is insoluble in water, has low volatility, is odorless, has good compatibility with polysiloxane, and does not affect transparency, and has the following structure: (CH2=CH)3-SiO-(Si(CH3)(CH=CH2)O) n -Si(CH=CH2)3, where n is 0 or an integer from 1 to 20. Most preferably: (CH2=CH)3-SiO-(Si-(CH3)(CH=CH2)O)8-Si(CH=CH2)3, CH2=CH-Si(CH3)2-O-(Si(CH3)(CH=CH2)O)8-Si(CH3)2-CH=CH2, and / or (CH3)3SiO-(Si-(CH3)(CH=CH2)O)8-Si(CH3)3.

[0037] Preferably, the catalyst is selected from platinum group metals known in the art, including platinum group metals (elemental substances) such as platinum (including platinum black), rhodium and palladium; platinum chlorides such as H2PtCl4·kH2O, H2PtCl6·kH2O, NaHPtCl6·kH2O, KHPtCl6·kH2O, Na2PtCl6·kH2O, K2PtCl4·kH2O, PtCl4·kH2O, PtCl2, Na2HPtCl4·kH2O, (wherein k is an integer from 0 to 6, and preferably 0 or 6), chloroplatinic acid and chloroplatinic acid salts; alcohol-modified chloroplatinic acid; complexes of chloroplatinic acid with olefins; platinum-vinylsiloxane complexes (Karstedt, Karstedt catalyst); platinum group metals such as platinum black and palladium loaded on carriers such as alumina, silica and carbon; rhodium-olefin complexes; chlorotris(triphenylphosphine)rhodium (Wilkinson catalyst); complexes of platinum chloride, chloroplatinic acid and chloroplatinic acid salts with vinyl-containing siloxanes, particularly preferably complexes of platinum with vinyl-containing polysiloxanes.

[0038] In the present application, the amount of the platinum group metal-containing catalyst added is based on the amount required to effectively catalyze the hydrosilylation reaction, and based on the total mass of the vinyl polysiloxane and the hydrogen-containing polysiloxane, the amount of the platinum group metal added as a catalyst is typically in the range of 0.1-500 ppm, preferably 0.5-200 ppm, and more preferably 1.5-25 ppm.

[0039] The second aspect of the present invention also discloses metal-coated silicone elastomer microspheres obtained according to the preparation method as described above.

[0040] The third aspect of the present invention also discloses the use of the metal-coated silicone elastomer microspheres as described above in conductive coatings or conductive adhesives.

[0041] Compared with the prior art, in which the surface of organic microspheres is coated with the commonly used heavy metal stannous chloride for sensitization, noble metal palladium chloride and hydrochloric acid for activation, and then dangerous substances such as formaldehyde and sodium borohydride are used for reduction, the metal-coated organic silicon elastomer composite microspheres and the preparation method and use thereof of the present invention have the following beneficial effects:

[0042] 1) From the perspective of preparation method, it has the advantages of environmental protection, safety, simple process and easy control, and is suitable for large-scale production.

[0043] 2) The metal-coated silicone elastomer composite microspheres finally prepared have the advantages of light weight, high and low temperature resistance, aging resistance, high conductivity, hard shell and soft core, high sphericity, good fluidity, etc., and the cost is greatly reduced compared to pure silver.

[0044] 3) The metal-coated silicone elastomer microspheres claimed in this application can well meet the uses or potential uses such as conductive coatings, conductive adhesives, low-temperature photovoltaic silver pastes, electromagnetic shielding, thermal conductivity, and toughening. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Shown is a SEM image of the product prepared in Example 1 of the present invention.

[0046] Figure 2 Shown is a SEM image of the product prepared in Example 2 of the present invention.

[0047] Figure 3 Shown is a SEM image of the product prepared in Example 3 of the present invention.

[0048] Figure 4 Shown is a SEM image of the product prepared in Example 4 of the present invention.

[0049] Figure 5 Shown is the SEM image of the product prepared in Comparative Example 1 of the present invention.

[0050] Figure 6 Shown is the SEM image of the product prepared in Comparative Example 2 of the present invention.

[0051] Figure 7 Shown is the SEM image of the product prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0052] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0053] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0054] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of implementation of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of implementation of the present invention without substantially changing the technical content.

[0055] In a further embodiment, a specific method of preparing silicone elastomer microspheres having carbon-carbon double bonds and hydroxyl groups on the surface provided in the present invention is as follows:

[0056] Mixing a formulated amount of a liquid silicone composition, a curing retarder, a platinum group metal catalyst, and allyl methacrylate or allyl acrylate uniformly to form a first mixture; the liquid silicone composition comprises vinyl polysiloxane and hydrogen-containing polysiloxane;

[0057] uniformly mixing a formulated amount of surfactant and water to form a second mixture;

[0058] mixing the first mixture and the second mixture and emulsifying them to a desired particle size through an emulsifying device;

[0059] The organic silicone droplets in the emulsion are heated in a water bath at room temperature of 25-100°C to solidify into organic silicone elastomer microspheres having allyl methacrylate or allyl acrylate on the surface.

[0060] In a specific embodiment, the surfactant is selected from one or more of nonionic surfactants, cationic surfactants, anionic surfactants or amphoteric surfactants. In a more preferred embodiment, the nonionic surfactant includes one or more selected from polyoxyethylene alkyl ethers, polyoxyethylene polyoxypropylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyethylene glycol fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitol fatty acid esters, glycerol fatty acid esters, polyoxyethylene glycerol fatty acid esters, polyglycerol fatty acid esters, propylene glycol fatty acid esters, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, polyoxyethylene hydrogenated castor oil fatty acid esters, polyoxyethylene alkylamines, polyoxyethylene fatty acid amides, polyoxyethylene modified organopolysiloxanes and polyoxyethylene polyoxypropylene-modified organopolysiloxanes. In a more preferred embodiment, the anionic surfactant includes one or more selected from alkyl sulfates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkylphenyl ether sulfates, N-acyl taurates, alkylbenzene sulfonates, polyoxyethylene alkylphenyl ether sulfonates, α-olefin sulfonates, alkylnaphthalene sulfonates, alkyl diphenyl oxide disulfonates, dialkyl sulfosuccinates, monoalkyl sulfosuccinates, polyoxyethylene alkyl ether sulfosuccinates, fatty acid salts, polyoxyethylene alkyl ether acetates, N-acyl amino acid salts, N-acyl alanine salts, alkenyl succinates, alkyl phosphates and polyoxyethylene alkyl ether phosphates. In a more preferred embodiment, the amphoteric surfactant includes one or more selected from alkyl dimethylamine oxide, carboxy betaine, alkyl amide propyl dimethyl hydroxy betaine and alkyl hydroxy sulfo betaine.

[0061] The above surfactants can be used alone or in combination of two or more. Considering that non-ionic surfactants have substantially no adverse effect on the platinum group metal catalyst system, non-ionic surfactants are preferably used.

[0062] In a preferred embodiment, the amount of the surfactant is up to 20 wt % based on the total weight of the vinyl polysiloxane and the hydrogen polysiloxane. If the amount is too much, too many non-silicone impurities will be introduced, and if the amount is less than 0.01 wt %, it is very difficult to emulsify into microspheres, so the amount is preferably 0.01-15 wt %, and more preferably 0.1-10 wt % of the weight of the liquid silicone composition.

[0063] In a preferred embodiment, the amount of water used is 50 to 1000 wt % based on the total mass of the vinyl polysiloxane and the hydrogen-containing polysiloxane.

[0064] Emulsification can be carried out using emulsification equipment commonly used in the art, such as: high-speed rotary shear emulsifier, high-pressure jet emulsifier, colloid mill and ultrasonic emulsifier, etc., or a simple dispersion disk can be used to prepare the emulsification by the phase inversion method well known in the industry.

[0065] The addition curing reaction can be carried out at room temperature or by heating the emulsion to a temperature not higher than 100°C.

[0066] In a further embodiment, a specific method of functional group modification a) provided in the present invention is as follows:

[0067] The grafted material is added into a water dispersion system of organic silicon elastomer microspheres having carbon-carbon double bonds and hydroxyl groups on the surface and polymerization is initiated.

[0068] This modification can be followed by filtration to remove impurities.

[0069] In a preferred embodiment, the grafted substance is selected from monomers containing one or more of a primary amine group, a secondary amine group, a tertiary amine group, an ester group, a thiol group, an olefin group, a hydroxyl group, an amide group, and a carbonyl group.

[0070] In a preferred embodiment, the graft is selected from one or more of tris(2-hydroxyethyl) isocyanurate tripropylene, isocyanurate triallyl, methacrylate-2-dimethylaminoethyl, 3-dimethylaminopropyl methacrylamide; and / or, the graft is selected from one or more of ethylene glycol di(3-mercaptopropionate), 1,4-butanediol di(3-mercaptopropionate), trimethylolpropane tri(3-mercaptopropionate), pentaerythritol tetra(3-mercaptopropionate). Considering the low cost, availability and low odor of the product, the graft containing thiol is not selected. In a most preferred embodiment, the graft is selected from one or two of tris(2-hydroxyethyl) isocyanurate tripropylene and isocyanurate triallyl.

[0071] In one embodiment, when initiating polymerization, the initiator is selected from one or more of high-energy ray source irradiation, water-soluble persulfate initiator, oxidation-reduction initiation system, water-soluble azo initiator, and thermal initiation polymerization.

[0072] In a preferred embodiment, the high energy ray source is selected from a cobalt source, X-rays, ultraviolet rays, and a high energy electron accelerator. In a more preferred embodiment, the irradiation dose is 0.1 Mrad to 35 Mrad, and more preferably, the irradiation dose is 1.0 Mrad to 15.0 Mrad.

[0073] In another preferred embodiment, the initiator is selected from one or more of a water-soluble persulfate initiator, an oxidation-reduction initiation system and a water-soluble azo initiator. In this preferred embodiment, the amount of the initiator is 0.001wt% to 30wt% of the amount of the graft. For example, it can be 0.1wt%, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%. In a more preferred embodiment, the water-soluble persulfate initiator is selected from one or more combinations of potassium persulfate, sodium persulfate and ammonium persulfate. In a more preferred embodiment, the redox initiator system is selected from benzoyl peroxide / sucrose, tert-butyl hydroperoxide / sodium formaldehyde sulfoxylate, tert-butyl hydroperoxide / sodium metabisulfite, benzoyl peroxide / N,N-dimethylaniline, hydrogen peroxide / tartaric acid, hydrogen peroxide / sodium formaldehyde sulfoxylate, ammonium persulfate / ferrous sulfate, hydrogen peroxide / ferrous sulfate, benzoyl peroxide / / N,N-diethylaniline, benzoyl peroxide / ferrous pyrophosphate, potassium persulfate / silver nitrate, persulfate / thiol, cumene hydroperoxide / ferrous chloride, persulfate / ferrous chloride, Potassium sulfate / ferrous chloride, hydrogen peroxide / ferrous chloride, isopropylbenzene hydroperoxide / tetraethyleneimine, ammonium persulfate-sodium bisulfite, potassium persulfate-sodium bisulfite, ammonium persulfate-ferrous sulfate, hydrogen peroxide-ferrous sulfate, ammonium persulfate-ferrous chloride, hydrogen peroxide-ferrous chloride, potassium persulfate-silver nitrate, persulfate-thiol, hydrogen peroxide-ferrous sulfate, tert-butyl hydroperoxide-sodium formaldehyde sulfoxylate, ammonium persulfate-sodium formaldehyde sulfoxylate, potassium persulfate-sodium formaldehyde sulfoxylate, sodium persulfate-sodium formaldehyde sulfoxylate. In a more preferred embodiment, the water-soluble azo initiator is selected from azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid, azobisisopropylimidazoline.

[0074] In another preferred embodiment, the thermal initiation temperature is 90°C to 100°C, such as 90°C, 93°C, 95°C, 97°C, 100°C, etc.

[0075] In a more specific embodiment, a redox initiation system with low energy consumption and little residual monomer is selected.

[0076] Furthermore, a specific method b) of functional group modification provided in the present invention is as follows:

[0077] The organic silicon elastomer microspheres containing carbon-carbon double bonds and hydroxyl groups on the surface are further treated with one or both of nitrogen-containing silane and sulfur-containing silane.

[0078] In one embodiment, the sulfur-containing silane is selected from any one or more of the following: bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-thiocyanatopropyltriethoxysilane, 3-thiocyanatopropyltriethoxysilane, 3-octanoylthiopropyltrimethoxysilane, 3-octanoylthiopropyltriethoxysilane, and the structural formulas are respectively Silane containing both nitrogen and sulfur elements and the structural formula is Silanes containing both nitrogen and sulfur, where R 1 is a straight-chain or branched saturated hydrocarbon group containing 3 to 12 carbon atoms, R, R 2 is methyl or ethyl, and n is an integer of 2 to 10. Considering the availability and hydrolysis of the product, in a preferred embodiment, the sulfur-containing silane is selected from one or more of bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide and 3-mercaptopropyltrimethoxysilane.

[0079] In one embodiment, the nitrogen-containing silane is selected from any one or more of the following: 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-n-butyl-3-aminopropyltrimethoxysilane, N-n-butyl-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, One or more of ethoxysilane, 3-anilinopropyltrimethoxysilane, 3-anilinopropyltriethoxysilane, 3-(N-cyclohexylamino)propyltrimethoxysilane, 3-(N-cyclohexylamino)propyltriethoxysilane, 3-(N-cyclohexylamino)propylmethyldimethoxysilane, 3-(N-cyclohexylamino)propylmethyldiethoxysilane, 3-ureapropyltrimethoxysilane, 3-ureapropyltriethoxysilane, N,N-dimethyl-3-aminopropyltrimethoxysilane, N,N-diethyl-3-aminopropyltrimethoxysilane, 3-(diethylenetriamine)propyltrimethoxysilane, and N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane. Taking into account low cost, availability, easy hydrolysis and stability after hydrolysis, in a more preferred embodiment, the nitrogen-containing silane is selected from one or more of 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and 3-ureapropyltrimethoxysilane.

[0080] In one embodiment, the treatment temperature is 50-100°C, preferably 60-90°C, more preferably 70-80°C.

[0081] In one embodiment, the treatment is accompanied by ultrasound and / or stirring.

[0082] In one embodiment, the treatment time is at least 10 min, such as 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, or 90 min.

[0083] In a further embodiment, the functional group modification in the present invention comprises at least b). In a most specific embodiment, the functional group modification in the present invention is firstly performed in a) and then in b).

[0084] In a further embodiment, the method of completing the deposition and / or coating of metal on the surface of the silicone elastomer microspheres includes one of the following methods:

[0085] A) during stirring, adding a silver complex solution and a stabilizer to an aqueous suspension of functional group-modified organosilicon elastomer microspheres, stirring evenly to form a mixture; maintaining stirring and controlling the temperature, and dripping a reducing agent aqueous solution into the mixture to complete the deposition and coating of the metal on the surface of the microspheres;

[0086] B) adding a reducing agent aqueous solution and a stabilizer to an aqueous suspension of the functional group-modified organosilicon elastomer microspheres, stirring evenly to form a mixture; maintaining stirring and controlling the temperature, and dripping a silver salt complex solution into the mixture to complete the deposition and coating of the metal on the surface of the microspheres;

[0087] C) adding a stabilizer to the aqueous suspension of the functional group-modified silicone elastomer microspheres, stirring evenly to form a mixture; maintaining stirring and controlling the temperature, and simultaneously dropping a silver salt complex solution and an aqueous solution of a reducing agent into the mixture to complete the deposition and coating of the metal on the surface of the microspheres.

[0088] Considering the simplicity and safety of the process, process A) is preferred.

[0089] In one embodiment of the present invention, the metal salt is selected from one or more of nitrates, acetates, fluorides, and perchlorates. In a specific embodiment, the silver salt is selected from one or more of silver nitrate, silver acetate, silver fluoride, and silver perchlorate, preferably one or more of silver nitrate and silver acetate.

[0090] In one embodiment of the present invention, the complexing agent is selected from one or more of ammonia, ethylenediamine, hexamethylenediamine, triethylamine, n-butylamine, alcoholamines, sodium citrate, sodium potassium citrate, disodium EDTA, citric acid, tartaric acid, gluconic acid, malic acid, and lactic acid. In one embodiment, the alcoholamines are selected from one or more of ethanolamine, propanolamine, and butanolamine. In view of low cost and availability, one or more of ammonia, ethanolamine, hexamethylenediamine, and isobutanolamine are preferred.

[0091] In one embodiment of the present invention, the reducing agent is selected from one or more of hydrazine hydrate, sodium borohydride, dimethylamino borane, formaldehyde, acetaldehyde, glucose, ascorbic acid, tartaric acid, glycerol, ferrous sulfate, sodium hypophosphite, sodium hypophosphite, hydrogen peroxide, and sodium sulfite. In view of non-toxicity, environmental protection, availability, easy treatment of subsequent wastewater, and low cost, one or more of glucose and ascorbic acid are preferred.

[0092] In one embodiment of the present invention, the stabilizer is selected from one or more of polyvinyl pyrrolidone, arabic plastic, polyvinyl alcohol, sodium citrate, and sodium thiosulfate. Polyvinyl pyrrolidone or polyvinyl alcohol is preferred. Preferably, the number average molecular weight of the polyvinyl pyrrolidone or polyvinyl alcohol is preferably 3,500 to 1.8 million, more preferably 30,000 to 630,000, such as 5W, 8W, 10W, 12W, 15W, 20W, 25W, 30W, 35W, 40W, 45W. The number average molecular weight is tested by GPC.

[0093] According to the different particle sizes and specific surface areas of the microspheres, if the proportion of silver is too small, the coating is incomplete, and if the proportion of silver is too large, excessive coating is formed, which results in high cost. In a preferred embodiment, the weight ratio of the metal (such as silver) to the silver-organic silicone elastomer composite microspheres is 60-98wt%, preferably 65%-95wt%; the corresponding volume ratio is 19-65%, and the specific gravity ratio is 2.78-7.2g / cm 3 For example, the weight ratio may be 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%. For example, the volume ratio may be 20%, 25%, 30%, 32%, 35%, 38%, 40%, 45%. The specific gravity may be 2.5g / cm 3 , 3g / cm 3 , 3.5g / cm 3 , 4g / cm 3 4.5g / cm 3 , 5g / cm 3 , 5.5g / cm 3 , 6g / cm 3 、6.5g / cm 3 , 7g / cm 3 .

[0094] The ratio of reducing agent to silver nitrate is determined according to the type of reducing agent selected to ensure that the silver nitrate is completely reduced to metallic silver.

[0095] According to the selected complexing agent, the ratio of the complexing agent to silver nitrate is determined to ensure that the silver nitrate is completely complexed to form a stable complex.

[0096] Depending on the selected stabilizer, the ratio of stabilizer to silver nitrate is determined to ensure a stable reaction process.

[0097] In one embodiment of the present invention, after the metal is deposited and / or coated on the surface of the organosilicon elastomer microspheres, the solid and liquid are separated and vacuum drying is performed.

[0098] The technical scheme and technical effects of the present invention are further described and explained through the following specific embodiments and implementation effects.

[0099] Example 1

[0100] This embodiment is a specific silver-coated silicone elastomer microsphere and a preparation method thereof.

[0101] 1) The raw materials include: 100 parts by weight of a vinyl silicone oil and hydrogen silicone oil composition having a viscosity of 200 cSt at 25°C, a vinyl content of 1.45% (by weight), and a hydrogen content of 0.09% (by weight); 1.5 parts by weight of a composition having a structure of

[0102] (CH2=CH)3-SiO-(Si-(CH3)(CH=CH2)O)8-Si(CH=CH2)3 curing retarder, 1.1 parts by weight of allyl methacrylate, 0.20 parts by weight of chloroplatinic acid-olefin complex with a platinum content of 3000ppm, 5.0 parts by weight of isomeric alcohol polyoxyethylene ether with an HLB value of 11.0, and 100 parts by weight of deionized water;

[0103] The above raw materials were circulated through a homogenizer at 30 MPa and emulsified for 10 minutes to form an emulsion with an average particle size (D50) of 1.70 μm;

[0104] 2) The mixture was kept in a water bath at 48° C. for 40 hours to complete the preparation of an organic silicone elastomer aqueous dispersion having an average particle size (D50) of 1.72 μm and a solid content of 51.99% and containing carbon-carbon double bonds and hydroxyl functional groups on the surface, wherein the molar ratio of hydrogen bonds to double bonds was 1.442.

[0106] 3) nitrogen is introduced into the above-mentioned aqueous dispersion of silicone elastomer to deoxygenate for 60 minutes, and 13% of triallyl isocyanurate based on the weight of silicone elastomer microspheres and 0.7% of ammonium persulfate based on the weight of triallyl isocyanurate are added, and the mixture is stirred for 45 minutes. The mixture is heated to 86° C., and sodium bisulfite based on the weight of triallyl isocyanurate is added at 0.45%. After the addition, the mixture is stirred and kept warm for 5 hours to complete the grafting, and impurities are removed by filtration.

[0107] 4) Add 6% of bis-[3-(triethoxysilyl)-propyl]-disulfide and 9% of 3-aminopropyltriethoxysilane by solid weight to the above-mentioned result, heat and stir at 80°C for 2 hours to complete the bonding of sulfur-containing silane and nitrogen-containing silane to the surface hydroxyl groups of the silicone elastomer microspheres.

[0108] 5) Filtration to obtain a filter cake of surface functionalized silicone elastomer microspheres having a solid content of 65.05%.

[0109] 6) Take 1.35 g of the functionalized silicone elastomer microsphere filter cake having a solid content of 65.05%, add 25 g of deionized water and stir to form a suspension;

[0110] 7) Take 6.5 grams of silver nitrate and dissolve it in 25 grams of deionized water. Stir until the solution is completely dissolved. Add hexamethylenediamine dropwise. The solution first turns yellow, then turns black and a black precipitate appears. Continue to add dropwise until the black precipitate disappears and becomes a transparent liquid to form a silver ammonia solution. Add 0.65 grams of PVP (polyvinyl pyrrolidone K30) and continue to stir until the PVP is dissolved.

[0111] 8) Add the mixture of 7) into the mixture of 6) all at once, stirring continuously;

[0112] 9) dissolving 8.6 g of glucose in 21.4 g of deionized water to form a 30 g glucose aqueous solution;

[0113] 10) 30 g of the glucose aqueous solution prepared in 9) was added dropwise to the stirred mixture in 7) over 3.5 hours, with continuous stirring and the temperature maintained between 20-30°C.

[0114] 11) After the addition is complete, stirring is continued for 25 hours to complete the reaction, during which the temperature is maintained between 20-30°C.

[0115] 12) Filter and vacuum dry to obtain silver-coated silicone elastomer microspheres.

[0116] The specific gravity of the silver-coated silicone elastomer microspheres prepared in this example is: 3.94 g / cm 3 , of which silver accounts for 30.93% of the volume. In contrast, the specific gravity of pure silver microspheres is 10.5g / cm 3 , silver accounts for 100% of the volume.

[0117] The silver layer of the silver-coated silicone elastomer microspheres in this embodiment is completely, densely and continuously coated, and the product has good spherical shape. Figure 1 .

[0118] Example 2

[0119] This embodiment is a specific silver-coated silicone elastomer microsphere and a preparation method thereof.

[0120] 1) 100 parts by weight of a vinyl compound having a viscosity of 3000 cSt at 25°C, a vinyl content of 1.30% by weight, and a hydrogen content of 0.1% by weight

[0121] Silicone oil and hydrogen-containing silicone oil composition; 1.2 parts by weight Structure:

[0122] A curing retarder of CH2=CH-Si(CH3)2-O-(Si(CH3)(CH=CH2)O)8-Si(CH3)2-CH=CH2; 0.18 parts by weight of a Karstedt catalyst with a platinum content of 3000ppm; 2.0 parts by weight of allyl methacrylate are first mixed evenly, and then 6.0 parts by weight of polyoxyethylene lauryl ether with an HLB value of 12 are added and mixed evenly.

[0123] 2) The rotation speed was increased to 6000 rpm, and 11.0 parts by weight of water was added dropwise under stirring to complete phase inversion emulsification, and then 89 parts of water was added at 500 rpm and stirred evenly to form an emulsion with an average particle size (D50) of 2.1 microns, and then the emulsion was kept at 52° C. for 50 hours to complete the preparation of an organic silicone elastomer aqueous dispersion with an average particle size (D50) of 2.2 microns and a solid content of 51.58%. The molar ratio of hydrogen bonds to double bonds was 1.562.

[0124] 3) nitrogen was introduced into the above-mentioned aqueous dispersion of the silicone elastomer for deoxidation for 60 minutes, and 11.0% of tris(2-hydroxyethyl) tripropylene isocyanurate by weight of the silicone elastomer microspheres and 2.0% of tert-butyl hydroperoxide by weight of the tris(2-hydroxyethyl) tripropylene isocyanurate were added, and the mixture was stirred for 5 minutes, and then 11.0% of tris(2-hydroxyethyl) tripropylene isocyanurate by weight of the silicone elastomer microspheres were added.

[0125] 4) Add 2.5% of bis-[3-(triethoxysilyl)-propyl]-tetrasulfide and 7.8% of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane by weight of solid to the above-mentioned product, and ultrasonicate for 30 minutes to complete the bonding of sulfur-containing silane and nitrogen-containing silane with the surface hydroxyl groups of the organosilicon elastomer microspheres.

[0126] 5) Filtration to obtain a filter cake of surface functionalized silicone elastomer microspheres having a solid content of 69.03%.

[0127] 6) Take 1.25 g of the functionalized silicone elastomer microsphere filter cake with a solid content of 69.03%, add 25 g of deionized water and stir to form a suspension;

[0128] 7) Take 6.0 grams of silver nitrate and dissolve it in 25 grams of deionized water. Stir until the solution is completely dissolved. Add 28 wt% ammonia water dropwise. The solution first turns yellow, then turns black and a black precipitate appears. Continue to add until the black precipitate disappears and turns into a transparent liquid to form a silver ammonia solution. Add 0.61 grams of PVP (polyvinyl pyrrolidone K90) and continue to stir until the PVP is dissolved.

[0129] 8) Add the mixture of 7) into the mixture of 6) all at once, stirring continuously;

[0130] 9) dissolving 7.8 g of glucose in 22.2 g of deionized water to form a 30 g glucose aqueous solution;

[0131] 10) 30 g of the glucose aqueous solution prepared in 8) was added dropwise to the stirred mixture in 7) over 4.0 hours, with continuous stirring and the temperature maintained between 20-30°C.

[0132] 11) After the addition is complete, stirring is continued for 24 hours to complete the reaction, during which the temperature is maintained between 20-30°C.

[0133] 12) Filter and vacuum dry to obtain silver-coated silicone elastomer microspheres.

[0134] The specific gravity of the silver-coated silicone elastomer microspheres prepared in this example is: 3.81 g / cm 3 , of which silver accounts for 29.61% of the volume. In contrast, the specific gravity of pure silver microspheres is 10.5g / cm 3 , silver accounts for 100% of the volume.

[0135] The silver layer of the silver-coated silicone elastomer microspheres prepared in this embodiment is completely, densely and continuously coated, and the product has good spherical shape. Figure 2 shown.

[0136] Example 3

[0137] This embodiment is a specific silver-coated silicone elastomer microsphere and a preparation method thereof.

[0138] 1) 100 parts by weight of a vinyl silicone oil and hydrogen silicone oil composition having a viscosity of 600 cSt at 25°C, a vinyl content of 1.3% (by weight), and a hydrogen content of 0.055% (by weight); 1.1 parts by weight of a curing retarder having a structure of (CH3)3SiO-(Si-(CH3)(CH=CH2)O)8-Si(CH3)3; 0.15 parts by weight of a chloroplatinic acid-olefin complex having a platinum content of 3000 ppm; and 1.0 parts by weight of allyl acrylate, which are first mixed uniformly;

[0139] 2) Add 6 parts by weight of branched isomeric tridecanol polyoxyethylene ether with an HLB value of 12.0; 100 parts by weight of water, and

[0140] 1. The colloid mill was sheared for 10 min at 10000 rpm to form an emulsion with an average particle size (D50) of 3.0 μm.

[0141] 3) The mixture was kept in a water bath at 52° C. for 45 hours to complete the preparation of an organic silicon elastomer aqueous dispersion having an average particle size (D50) of 3.1 μm and a solid content of 51.75%, wherein the molar ratio of hydrogen bonds to double bonds was 1.528.

[0142] 4) nitrogen was introduced into the above-mentioned aqueous dispersion of the silicone elastomer to deoxidize for 60 minutes, and the weight of the silicone elastomer microspheres was 2.34 g / cm2.

[0143] 7.9% of tris(2-hydroxyethyl) tripropylene isocyanurate was added to the silicone elastomer aqueous dispersion, the temperature was raised to 65°C, and the mixture was stirred for 30 minutes. Then, 1.5% of diisopropylbenzene hydroperoxide by weight of tris(2-hydroxyethyl) tripropylene isocyanurate was added, and the mixture was stirred for 10 minutes. Then, 1.0% of sodium formaldehyde sulfoxylate by weight of tris(2-hydroxyethyl) tripropylene isocyanurate was added, and the mixture was stirred and kept warm at 65°C for 2 hours to complete the grafting, and the impurities were removed by filtration.

[0144] 5) Add 6.5% of 3-mercaptopropyltrimethoxysilane and 8.0% of 3-aminopropyltriethoxysilane by solid weight to the above-mentioned result, heat and stir at 75° C. for 2 hours to complete the bonding of sulfur-containing silane and nitrogen-containing silane to the surface hydroxyl groups of the silicone elastomer microspheres.

[0145] 6) Filter by suction to obtain a filter cake of surface functionalized silicone elastomer microspheres having a solid content of 68.7%.

[0146] 7) Take 1.5 g of the functionalized silicone elastomer microsphere filter cake with a solid content of 68.7%, add 25 g of deionized water and stir to form a suspension;

[0147] 8) Take 6.7 grams of silver nitrate and dissolve it in 25 grams of deionized water. Stir until the solution is completely dissolved. Add 28% ammonia water dropwise. The solution first turns yellow, then turns black and a black precipitate appears. Continue to add until the black precipitate disappears and turns into a transparent liquid to form a silver ammonia solution. Add 0.65 grams of PVP (polyvinyl pyrrolidone K60) and continue to stir until the PVP is dissolved.

[0148] 9) Add the mixture in 8) into the mixture in 7) all at once, stirring continuously.

[0149] 10) Dissolve 4.0 g of ascorbic acid in 26 g of deionized water to form 30 g of ascorbic acid aqueous solution.

[0150] 11) 30 g of the ascorbic acid aqueous solution prepared in 10) was added dropwise to the stirred mixture in 7) over 4.0 hours, with continuous stirring and the temperature maintained between 20-30°C.

[0151] 12) After the dropwise addition is completed, stirring is continued for 6.0 hours to complete the reaction, during which the temperature is maintained between 25-30°C.

[0152] 13) Filter and vacuum dry to obtain silver-coated silicone elastomer microspheres.

[0153] The specific gravity of the silver-coated silicone elastomer microspheres obtained in this example is 3.68 g / cm 3 , of which silver accounts for 28.23% of the volume. In contrast, the specific gravity of pure silver microspheres is 10.5g / cm 3 , silver accounts for 100% of the volume. The silver layer is complete, dense and continuous, and the product has good spherical shape. See the specific SEM picture Figure 3 shown.

[0154] Example 4

[0155] This embodiment is a specific silver-coated silicone elastomer microsphere and its preparation method. It is only the functional group modification without the grafting or copolymerization treatment of step a), and only the step b) treatment is performed. It includes the following steps:

[0156] 1) Take the organic silicone elastomer aqueous dispersion with an average particle size (D50) of 2.2 μm and a solid content of 51.58% prepared in Example 2, without grafting, and directly add 2.5% of bis-[3-(triethoxysilyl)-propyl]-tetrasulfide and 7.8% of 3-ureapropyltrimethoxysilane by solid weight, and ultrasonicate for 30 minutes to complete the bonding of sulfur-containing silane and nitrogen-containing silane to the surface hydroxyl groups of the organic silicone elastomer microspheres.

[0157] 2) Filtration to obtain a filter cake of surface functionalized silicone elastomer microspheres having a solid content of 69.03%.

[0158] 3) taking 1.25 g of the functionalized silicone elastomer microsphere filter cake having a solid content of 69.03%, adding 25 g of deionized water and stirring to form a suspension;

[0159] 4) Take 6.0 grams of silver nitrate and dissolve it in 25 grams of deionized water. Stir until the solution is completely dissolved. Add 28% ammonia water dropwise. The solution first turns yellow, then turns black and a black precipitate appears. Continue to add until the black precipitate disappears and turns into a transparent liquid to form a silver ammonia solution. Add 0.61 grams of PVP (polyvinyl pyrrolidone K90) and continue to stir until the PVP is dissolved.

[0160] 5) Add the mixture in 4) into the mixture in 3) all at once, stirring continuously.

[0161] 6) Dissolve 7.8 grams of glucose in 22.2 grams of deionized water to form a 30-gram glucose aqueous solution.

[0162] 7) 30 g of the glucose aqueous solution prepared in 6) was added dropwise to the stirred mixture in 5) over 4.0 hours, with continuous stirring and the temperature maintained between 20-30°C.

[0163] 8) After the addition is complete, stirring is continued for 24 hours to complete the reaction, during which the temperature is maintained between 20-30°C.

[0164] 9) Filter and vacuum dry to obtain silver-coated silicone elastomer microspheres.

[0165] The specific gravity of the silver-coated silicone elastomer microspheres prepared in this example is: 3.81 g / cm 3 , of which silver accounts for 29.61% of the volume. In contrast, the specific gravity of pure silver microspheres is 10.5g / cm 3 , silver accounts for 100% of the volume.

[0166] The silver coating of the silver-coated silicone elastomer microspheres prepared in this embodiment is: partially complete, dense, and continuous, but many are defective and partially incomplete, but the overall product has a good spherical shape. Figure 4 .

[0167] Comparative Example 1

[0168] The mixture of pure organosilicon elastomer microspheres prepared in Example 1 and water was taken, and no grafting, copolymerization, or surface treatment with amino or sulfur-containing silane was performed. It was directly filtered to obtain a pure organosilicon elastomer microsphere filter cake with a solid content of 60.5%.

[0169] Next, the same process as in Example 1 is used to coat the metallic silver:

[0170] 1) Take 1.45 g of the above-mentioned pure silicone elastomer microsphere filter cake with a solid content of 60.5% (the actual solid content is consistent with that in Example 1), add 25 g of deionized water and stir to form a suspension.

[0171] 2) Take 6.5 grams of silver nitrate and dissolve it in 25 grams of deionized water. Stir until the solution is completely dissolved. Add hexamethylenediamine dropwise. The solution first turns yellow, then black and a black precipitate appears. Continue to add until the black precipitate disappears and becomes a transparent liquid to form a silver ammonia solution. Add 0.65 grams of PVP (polyvinyl pyrrolidone K30) and continue to stir until the PVP is dissolved.

[0172] 3) Add the mixture from 2) into the mixture from 1) all at once, stirring continuously.

[0173] 4) Dissolve 8.6 grams of glucose in 21.4 grams of deionized water to form 30 grams of glucose aqueous solution.

[0174] 5) 30 g of the glucose aqueous solution prepared in 4) was added dropwise to the stirred mixture in 3) over 3.5 hours, with continuous stirring and the temperature maintained between 20-30°C.

[0175] 6) After the addition is complete, stirring is continued for 25 hours to complete the reaction, during which the temperature is maintained between 20-30°C.

[0176] Through this comparative example, it is found that the pure organic silicon microspheres are basically exposed, and few are coated. Silver is self-nucleated and not deposited on the surface of the spheres. See the specific SEM picture. Figure 5 .

[0177] Comparative Example 2

[0178] The functionalized silicone elastomer microsphere aqueous dispersion prepared in Example 2, which had been grafted and copolymerized with 11.0% by weight of tris(2-hydroxyethyl)tripropylene isocyanurate, was taken without using bis-[3-(triethoxysilyl)-propyl]-tetrasulfide and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane for surface treatment. It was directly filtered to obtain a functionalized silicone elastomer microsphere filter cake with a solid content of 65.9%.

[0179] Next, the same process as in Example 2 is used to coat the metallic silver:

[0180] 1) Take 1.31 g of the functionalized silicone elastomer microsphere filter cake with a solid content of 65.9% (the actual solid content is consistent with Example 2), add 25 g of deionized water and stir to form a suspension;

[0181] 2) Take 6.0 grams of silver nitrate and dissolve it in 25 grams of deionized water. Stir until the solution is completely dissolved. Add 28% ammonia water dropwise. The solution first turns yellow, then turns black and a black precipitate appears. Continue to add until the black precipitate disappears and turns into a transparent liquid to form a silver ammonia solution. Add 0.61 grams of PVP (polyvinyl pyrrolidone K90) and continue to stir until the PVP is dissolved.

[0182] 3) Add the mixture from 2) into the mixture from 1) all at once, stirring continuously.

[0183] 4) Dissolve 7.8 grams of glucose in 22.2 grams of deionized water to form a 30-gram glucose aqueous solution.

[0184] 5) 30 g of the glucose aqueous solution prepared in 4) was added dropwise to the stirred mixture in 3) over 4.0 hours, with continuous stirring and the temperature maintained between 20-30°C.

[0185] 6) After the addition is complete, stirring is continued for 24 hours to complete the reaction, during which the temperature is maintained between 20-30°C.

[0186] 7) Filter and dry in vacuum.

[0187] This comparative example found that some of the functionalized silicone elastomer microspheres were well coated, but some were damaged. Figure 6 shown.

[0188] Comparative Example 3

[0189] Take the silicone elastomer microspheres prepared in Example 3, which have been copolymerized with 7.9% by weight of tris(2-hydroxyethyl)tripropylene isocyanurate, and add 6.5% by weight of 3-mercaptopropyltrimethoxysilane, but no longer add 3-aminopropyltriethoxysilane. Heat and stir at 75°C for 2 hours.

[0190] The filter cake of surface-functionalized silicone elastomer microspheres with a solid content of 69.1% was obtained by suction filtration.

[0191] Next, the same process as in Example 3 is used to coat the metallic silver:

[0192] 1) Take 1.49 g of the functionalized silicone elastomer microsphere filter cake with a solid content of 69.1% (the actual solid content is consistent with that in Example 3), add 25 g of deionized water and stir to form a suspension;

[0193] 2) Take 6.7 grams of silver nitrate and dissolve it in 25 grams of deionized water. Stir until the solution is completely dissolved. Add 28% ammonia water dropwise. The solution first turns yellow, then turns black and a black precipitate appears. Continue to add until the black precipitate disappears and turns into a transparent liquid to form a silver ammonia solution. Add 0.65 grams of PVP (polyvinyl pyrrolidone K60) and continue to stir until the PVP is dissolved.

[0194] 3) Add the mixture from 2) into the mixture from 1) all at once, stirring continuously.

[0195] 4) Dissolve 4.0 g of ascorbic acid in 26 g of deionized water to form 30 g of ascorbic acid aqueous solution.

[0196] 5) 30 g of the ascorbic acid aqueous solution prepared in 4) was added dropwise to the stirred mixture in 3) over 4.0 hours, during which stirring was continued and the temperature was maintained between 20-30°C.

[0197] 6) After the addition is complete, stirring is continued for 6.0 hours to complete the reaction, during which the temperature is maintained between 25-30°C.

[0198] 7) Filter and vacuum dry to obtain silver-coated silicone elastomer microspheres.

[0199] This comparative example found that most of the composite balls were completely coated, but a few were still incomplete. Figure 7 The room temperature resistivity test of the products of the embodiment and the comparative example is shown.

[0200] The resistivity of the above-mentioned embodiment, comparative example and pure silver micron powder was tested respectively by using the ST-2722 semiconductor powder resistivity tester of Suzhou Jingge Electronics Co., Ltd. During the test, the sample to be tested was added and compacted with a pressure of 30 MPa. After testing, the resistivity results at room temperature are shown in Table 1:

[0201] Table 1

[0202]

[0203] Note: SF120 and FA-S-1 are 1.82 micron pure silver powders from American AMES and 1.30 micron pure silver powders from Japanese DOWA, respectively. It can be seen that compared with pure silver powder, under the same test equipment and test conditions, the resistivity of the silicone elastomer-silver composite powders prepared in Examples 1, 2, 3, and 4 is at the same order of magnitude as the resistivity of pure silver powders from well-known companies in the industry, and the resistivity of Examples 1, 2, and 3 is only slightly different from that of pure silver powder, and the specific gravity of the finished products of Examples 1, 2, and 3 is only 3.94 g / cm 3 、3.81g / cm 3 、3.68g / cm 3The specific gravity of the core material silicone elastomer is 1.0g / cm 3 ; Shell material: Pure silver, specific gravity: 10.5g / cm 3 , where the volume occupied by silver is 30.93%, 29.61%, and 28.23%, respectively, indicating that the approximate conductivity is achieved. The silver-coated silicone elastomer microspheres prepared in Examples 1, 2, and 3 can save 69.07%, 70.39%, and 71.77% of silver by volume, respectively. The cost is significantly reduced while the specific gravity is also greatly reduced. Moreover, it is less likely to settle when preparing conductive adhesives and conductive coatings.

[0204] Temperature resistance test:

[0205] Test conditions: within 1 hour, the temperature was raised from 250°C to 270°C, and the temperature was heated in a circulating oven under normal pressure and in an aerobic environment. The resistivity of the silver-coated silicone elastomer microspheres prepared in Examples 1, 2, and 3 after being subjected to the above-mentioned aerobic and high temperature tests is shown in Table 2, which shows that there is basically no change.

[0206] Table 2

[0207] sample Example 1 Example 2 Example 3 Pressure(Mpa) 30 30 30 Resistivity(Ω-cm) 3E-05 4E-05 3E-05

[0208] The curing temperature of photovoltaic low-temperature silver paste needs to be below 250°C when in use, otherwise it will cause damage to the solar panels. The above test results show that the silver-coated silicone elastomer microspheres prepared by this patent can meet the curing conditions of photovoltaic low-temperature silver paste.

[0209] In summary, the metal-coated silicone elastomer microspheres provided by the technical solution claimed in the present invention combine the dual advantages of silicone elastomer and conductive metal, and have good temperature resistance, have good use effects in the field of preparing conductive adhesives and conductive coatings, and have the advantages of low cost and low sedimentation compared to pure silver. Therefore, the present invention effectively overcomes various shortcomings in the prior art and has high industrial utilization value.

[0210] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing metal-coated silicone elastomer microspheres, characterized in that: The preparation method comprises the following steps: The surface of the silicone elastomer microspheres containing carbon-carbon double bonds and hydroxyl groups is modified with functional groups, wherein the functional groups include one or more of primary amine groups, secondary amine groups, tertiary amine groups, carboxyl groups, thiol groups, sulfur groups, hydroxyl groups, and carbonyl groups; then the microspheres are contacted with an aqueous solution containing a metal salt and a reducing agent and a reduction reaction occurs, thereby completing the deposition and / or coating of the metal on the surface of the silicone elastomer microspheres.

2. The preparation method according to claim 1, characterized in that: The method of preparing organic silicone elastomer microspheres containing carbon-carbon double bonds and hydroxyl groups comprises: mixing vinyl polysiloxane, hydrogen-containing polysiloxane, a curing retarder, and a platinum group metal catalyst, adding allyl methacrylate or allyl acrylate during the mixing, emulsifying and reacting in water.

3. The preparation method according to claim 2, characterized in that: Based on the total weight of the vinyl polysiloxane and the hydrogen-containing polysiloxane, the total amount of allyl methacrylate and / or allyl acrylate added is 0.5 to 20 wt %; and / or, the ratio of the molar number of hydrogen bonds in the hydrogen-containing polysiloxane to the molar number of vinyl groups in the vinyl polysiloxane is greater than 1:1, preferably 1.01 to 50:1, more preferably 1.2 to 2:1; and / or, the curing retarder is selected from one or more of alcohol derivatives having a carbon-carbon triple bond, ene-yne ​​compounds, alkenyl-containing polysiloxanes, amide compounds and maleate compounds; and / or, based on the total mass of the vinyl polysiloxane and the hydrogen-containing polysiloxane, the amount of the curing retarder added is 0.01 to 5 wt %; and / or the viscosity of the composition formed by the vinyl polysiloxane and the hydrogen-containing polysiloxane at 25° C. is not more than 100,000 mm 2 / s, preferably 50 to 10000 mm 2 / s; And / or, a surfactant is used during emulsification, wherein the surfactant is one or more selected from nonionic surfactants, cationic surfactants, anionic surfactants or amphoteric surfactants; preferably a nonionic emulsifier.

4. The preparation method according to claim 3, characterized in that: The amount of the surfactant is at most 20 wt %, preferably 0.01-15 wt %, based on the total mass of the vinyl polysiloxane and the hydrogen polysiloxane; And / or, the nonionic surfactant comprises one or more selected from polyoxyethylene alkyl ether, polyoxyethylene polyoxypropylene alkyl ether, polyoxyethylene alkylphenyl ether, polyethylene glycol fatty acid ester, sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, glycerol fatty acid ester, polyoxyethylene glycerol fatty acid ester, polyglycerol fatty acid ester, propylene glycol fatty acid ester, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, polyoxyethylene hydrogenated castor oil fatty acid ester, polyoxyethylene alkylamine, polyoxyethylene fatty acid amide, polyoxyethylene modified organopolysiloxane and polyoxyethylene polyoxypropylene-modified organopolysiloxane; and / or, the anionic surfactant comprises one or more selected from alkyl sulfates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkylphenyl ether sulfates, N-acyl taurates, alkylbenzene sulfonates, polyoxyethylene alkylphenyl ether sulfonates, α-olefin sulfonates, alkylnaphthalene sulfonates, alkyl diphenyl oxide disulfonates, dialkyl sulfosuccinates, monoalkyl sulfosuccinates, polyoxyethylene alkyl ether sulfosuccinates, fatty acid salts, polyoxyethylene alkyl ether acetates, N-acyl amino acid salts, N-acyl alanine salts, alkenyl succinates, alkyl phosphates and polyoxyethylene alkyl ether phosphates; and / or, the amphoteric surfactant comprises one or more of alkyl dimethylamine oxide, carboxy betaine, alkyl amidopropyl dimethyl hydroxy betaine and alkyl hydroxy sulfo betaine; And / or, the alcohol derivative having a carbon-carbon triple bond is one or more selected from 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 3-phenyl-1-butyn-3-ol and 1-ethyn-1-cyclohexyl alcohol; And / or, the enyne compound is selected from one or two of 3-methyl-3-pentene-1-yne and 3,5-dimethyl-3-hexene-1-yne; And / or, the alkenyl-containing low molecular weight polysiloxane is selected from one or two of tetramethyltetravinylcyclotetrasiloxane and tetramethyltetrahexenylcyclotetrasiloxane; and / or, the amide compound is selected from one or more of N,N-diallylformamide, N,N-diallylbenzamide, N,N,N',N'-tetraallylphthalamide, N,N,N',N'-tetraallylterephthalamide and N,N,N',N'-tetraallylisophthalamide; And / or, the maleate compound is selected from one or more of monoethyl maleate, monoallyl maleate, mono-2-ethylhexyl maleate and diallyl maleate.

5. The preparation method according to claim 1, characterized in that: The functional group modification is as follows: a) grafting or copolymerizing the grafted material with the carbon-carbon double bond; and / or b) utilizing the hydroxyl groups on the surface of the silicone elastomer microspheres as binding points, treating the silicone elastomer microspheres having carbon-carbon double bonds and hydroxyl groups on the surface with one or both of nitrogen-containing silanes and sulfur-containing silanes, and introducing amine groups and / or sulfur elements.

6. The preparation method according to claim 5, characterized in that: The grafted substance is selected from monomers containing one or more of primary amine groups, secondary amine groups, tertiary amine groups, thiol groups, alkenyl groups, hydroxyl groups, amide groups, and carbonyl groups; And / or, in a), an initiator is used to initiate the polymerization, and the initiator is selected from one or more of high-energy radiation source irradiation, water-soluble persulfate initiator, oxidation-reduction initiation system, water-soluble azo initiator, and thermal initiation polymerization; And / or, the nitrogen-containing silane is selected from any one or more of the following: 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-n-butyl-3-aminopropyltrimethoxysilane, N-n-butyl-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 3 -Aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-anilinopropyltrimethoxysilane, 3-anilinopropyltriethoxysilane, 3-(N-cyclohexylamino)propyltrimethoxysilane, 3-(N-cyclohexylamino)propyltriethoxysilane, 3-(N-cyclohexylamino)propylmethyldimethoxysilane, 3-(N-cyclohexylamino)propylmethyldiethoxysilane, 3-ureapropyltrimethoxysilane, 3-ureapropyltriethoxysilane, N,N-dimethyl-3-aminopropyltrimethoxysilane, N,N-diethyl-3-aminopropyltrimethoxysilane, 3-(diethylenetriamine) One or more of propyltrimethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane; preferably, the nitrogen-containing silane is selected from one or more of 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and 3-ureapropyltrimethoxysilane; And / or, the sulfur-containing silane is selected from any one or more of the following: bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-thiocyanatopropyltriethoxysilane, 3-thiocyanatopropyltriethoxysilane, 3-octanoylthiopropyltrimethoxysilane, 3-octanoylthiopropyltriethoxysilane, and the structural formulas are respectively Silane containing both nitrogen and sulfur elements has the structural formula Silanes containing both nitrogen and sulfur, where R 1 is a straight or branched saturated hydrocarbon group containing 3 to 12 carbon atoms, R 2 is methyl or ethyl, R is methyl or ethyl; n is an integer from 2 to 10; And / or, in b), the treatment temperature is 50-100°C.

7. The preparation method according to claim 1, characterized in that: The metal element in the metal and the metal salt is one or more selected from silver, nickel or zinc; And / or, the reducing agent is one or more selected from hydrazine hydrate, sodium borohydride, dimethylamino borane, formaldehyde, acetaldehyde, glucose, ascorbic acid, tartaric acid, glycerol, ferrous sulfate, sodium hypophosphite, sodium hypophosphite, hydrogen peroxide and sodium sulfite; And / or, the aqueous solution containing the metal salt and the reducing agent further contains one or more of a stabilizer and a complexing agent.

8. The preparation method according to claim 7, characterized in that: The stabilizer is selected from one or more of polyvinyl pyrrolidone, plastic arabic, polyvinyl alcohol, sodium citrate, and sodium thiosulfate; And / or, the complexing agent is selected from one or more of ammonia water, ethylenediamine, hexamethylenediamine, triethylamine, n-butylamine, alcohol amines, sodium citrate, sodium potassium citrate, disodium EDTA, citric acid, tartaric acid, gluconic acid, malic acid, and lactic acid; And / or, the metal salt is selected from one or more of nitrates, acetates, fluorides, and perchlorates; And / or, the silver salt is selected from one or more of silver nitrate, silver acetate, silver fluoride and silver perchlorate.

9. A metal-coated organosilicon elastomer microsphere obtained by the preparation method according to any one of claims 1 to 8; preferably, the volume ratio of the metal to the metal-coated organosilicon elastomer microsphere is 19-65wt%.

10. Use of the metal-coated silicone elastomer microspheres according to claim 9 in conductive coatings or conductive adhesives.

Citation Information

Cited By

  • Acrylic resin coated organic silicon elastomer PA (at) SE prepared by aqueous-phase suspension emulsion polymerization and preparation method and application of acrylic resin coated organic silicon elastomer PA (at) SE

    CN121824856A